Film Viewers' Motives and Satisfaction are Somewhere Laen (Uses and Gratification Analysis of the Palmgreen Model on Members of Imami UIN-Suka Yogyakarta) - Luthfi, Hamzah; Andryani, Kristina; Saputri, Dhea Octavia (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2025)
The film "Agak Laen" is the film that occupies the highest rating with 9.1 million viewers and is hotly discussed because the story is packaged in an interesting story and brings elements of comedy. This research discusses how a person's motives and satisfaction in watching a movie are "Agak Laen ". This study uses the Uses & Gratification theory of the Palm Green model which explains that individuals have the desired motives and satisfaction in accessing media. This study uses a qualitative descriptive method. Data collection was carried out by interviews with resource persons from IMAMI UIN-SUKA Yogyakarta. The results of this study show that the motive indicators (information, selfidentity, social interaction and entertainment) are met with the highest aspects of information and social interaction. The resource person stated that the audience's curiosity and interaction with the environment were the motivation to watch the film. Satisfaction indicators (information, self-identity, social interaction and entertainment) were also met with the highest aspects of entertainment and then social interaction generated after watching the movie "Agak Laen". The audience felt entertained and received a well conveyed message.